Sulfated Xyloglucan-Based Magnetic Nanocomposite for Preliminary Evaluation of Theranostic Potential - Casagrande-Denardin, J (ELSEVIER, 2022)
Chemically sulfated xyloglucan (S_XLG) was applied to encapsulate hydrophilic quercetin sulfate (Q_SO3) into superparamagnetic nanocomposites (MNSXQ_SO3) synthesized via interfacial polyaddition reaction. This nanoplatform was evaluated concerning in vitro antitumor activity, drug release profile, and magnetic behavior under a magnetic field. MNSXQ_SO3 exhibited antitumor activity against four human tumor cell lines: leukemia HL-60 (IC50 = 1.58 +/- 0.54 mu g mL(-1)), glioblastoma SNB-19 (IC50 = 8.77 +/- 0.36 mu g mL(-1)), colorectal carcinoma HCT-116 (IC50 = 8.69 +/- 0.21 mu g mL(-1)) and prostate PC3 (IC50 = 17.42 +/- 3.57 mu g mL(-1)). Additionally, MNSXQ_SO3 was able to delay the release of Q_SO3 (76 %) compared to the free Q_SO3 (100 %), after 48 h of drug delivery assay, revealing a release profile compatible with the Korsmeyer-Peppas kinetic model. These results represent a relevant progress in the production of multifunctional hybrid nanocarriers, providing a versatile nanocomposite with potential for targeted drug delivery and theranostic applications.